Respostas

2014-08-15T20:55:00-03:00
X + y = 4 
x*y = 29 

x = 4 - y 
x*y = 29 

---Substituindo na segunda: 

(4 - y)*y = 29 

4y - y² = 29 

- y² + 4y - 29 = 0 
Coeficientes: 
a = - 1 
b = 4 
c = - 29 

delta = b² - 4*a*c 
delta = 4² - 4*(- 1)*(- 29) 
delta = 16 - 116 
delta = - 100 

x1 = (- b + raiz de delta)/2a = (- 4 + raiz de (- 100))/2*(- 1) = (- 4 + 10i)/(- 2) = + 2 - 5i. 

x2 = (- b - raiz de delta)/2a = (- 4 - raiz de (- 100))/2*(- 1) = (- 4 - 10i)/(- 2) = 2 + 5i. 

S = {x E C / x = 2 - 5i ou x = 2 + 5i}.
2 5 2